PENGARUH PENDAPATAN DAN KECERDASAN SPIRITUAL TERHADAP PERSEPSI ETIS MAHASISWA DENGAN LOVE OF MONEY SEBAGAI VARIABEL INTERVENING - Arridla, Ahdaf (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
This study aimed to analyze the influence of income, gender on love of money. and the influence of spiritual intelligence, sex, love of money on ethical perception of students. This research was conducted at the Faculty of Economics, Accounting Department, State University of Surabaya. This type of research is quantitative descriptive. The sampling technique used in this research is proportional random sampling. The number of samples used were 146 respondents. Data analysis Structural Equation Modeling (SEM). The results showed that there was no significant relationship between the income of the love of money. There is a significant relationship between spiritual intelligence of students to the ethical perception of students. and there is significant influence between the love of money against the ethical perception of students